Assessment of the improvement of internal combustion engines cooling system using nanofluids and nanoencapsulated phase change materials. (June 2021) - Torregrosa, Antonio Jose; Broatch, Alberto; Olmeda, Pablo; Dreif, Amin
In recent years, due to the increasing need to reduce consumption of reciprocating internal combustion engines, new researches on different subsystems have raised. Among them, the use of nanofluids as a coolant medium seems to be an interesting alternative. In this work, the potential benefits of using nanofluids in the cooling system using an engine lumped model are studied. The methodology of the study starts with a whole description and validation of the model in both steady and transient conditions by means of a comparison with experimental results. Then, the potential benefits that could be obtained with the use of nanofluids are studied in a theoretical way. After that, the model is used to estimate the behavior of the system using different nanofluids in both stationary and transient conditions. The main results show that the advantages of using these new refrigerants are limited.